2007
DOI: 10.1103/physrevb.76.085106
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast photoinduced melting of spin-Peierls phase in the organic charge-transfer compounds alkali-tetracyanoquinodimethane

Abstract: Photoinduced phase transitions in spin-Peierls ͑SP͒ systems of alkali ͑M =K,Na͒-tetracyanoquinodimethane ͑TCNQ͒ have been studied by a reflection-type femtosecond ͑fs͒ pump-probe spectroscopy. The SP phase is destabilized by the generation of photocarriers through the breaking of the spin-singlet states in dimers. It results in the decrease of the dimeric molecular displacements within a few hundred of femtoseconds over several tens of TCNQ molecules. It is accompanied by the displacive-type coherent oscillati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 34 publications
5
35
1
Order By: Relevance
“…Such coherent oscillations have previously been reported in other examples of photoinduced phase transitions. [29][30][31][32][33][34][35] Here, let us briefly discuss semiquantitatively the amplitude of the coherent oscillation due to the JT mode, which is the largest among the four oscillations. As seen in the lower panel of Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Such coherent oscillations have previously been reported in other examples of photoinduced phase transitions. [29][30][31][32][33][34][35] Here, let us briefly discuss semiquantitatively the amplitude of the coherent oscillation due to the JT mode, which is the largest among the four oscillations. As seen in the lower panel of Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1 It is because a photoinduced phase transition in an ultrafast time scale may be used as a useful mechanism for future optical switching devices. Several transient photoinduced transitions between nearly degenerate two phases have been reported so far, e.g., insulator-metal transitions in VO 2 , 2 the neutral-ionic transition in tetrathiafulvalene-p-chloranil, 3,4 the charge-/ orbital-order insulator to ferromagnetic metal transition in the manganite, 5-7 the diamagnetic spin-Peierls phase to paramagnetic phase transition in K-tetracyanoquinodimethane, 8,9 and so on. In all of these transient photoinduced transitions, the conversion from one phase to another is not perfect, resulting to coexistence of original phase and the photoinduced phase.…”
Section: Introductionmentioning
confidence: 98%
“…In addition, they are the organic charge-transfer compounds [4][5][6][7][8][9][10][11]. Ikegami et al reported the pump-probe spectroscopy of K-and Na-TCNQ crystals in the IR region with 130 fs laser pulses generated by OPA [12,13]. They claimed that electron-hole pairs generated by photoexcitation melt the generalized Peierls phase to induce intermolecular coherent oscillations.…”
Section: Introductionmentioning
confidence: 99%